WHAT FACTORS INFLUENCE COLLEGE STUDENTS DECISION TO USE PAYLATER? - Adabiyah, Rofida Choirotul; Amalia, Husna; Faris, Sukron (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The presence of paylater as a payment system makes people shop in droves. This is due to user perceptions regarding money ownership, thereby encouraging consumptive behavior. In this quantitative-based research using primary data, researchers tested and studied the relationship between factors that are thought to influence paylater use. These factors are Islamic Financial Knowledge, Income, and Financial Management Behavior (FMB) as mediators. The population of this research is students in Malang City. With a sample of 100 respondents. The PLS-SEM method was used to test the data in this research. The results of this research reveal that income has a negative and significant effect, while Islamic Financial Behavior has a positive and significant effect on FMB. Furthermore, FMB has a positive and significant effect on Paylater Use. On the other hand, Income and Islamic Financial Knowledge both have a positive and insignificant influence on Paylater Use. The test results using mediating variables show a change in results, namely that Income has a negative and insignificant influence on Paylater Use which is tested through FMB, and Islamic Financial Behavior changes to have a positive and significant influence on Paylater Use which is tested through FMB